(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This study relates to the problematic aspects of integrating H ACC P standards. The purpose of the article is to study the application of H ACC P standards in enterprises and small business entities of public catering. The research methodology includes a systematic nature and is based on the systematization and analysis of scientific and research information in the field of safety standards at enterprises or business entities of public catering. The article shows that the procedures that must be developed and maintained for the safety of food products during their production are a key aspect of improving the environment. Research has found that 7 fundamental principles help in the development of plans H ACC P. As well as integration with the principles of risk management at a public catering enterprise.